Current evidence and new challenges in periprosthetic hip and knee fractures - Franceschini, Massimo; Pedretti, Leopoldo; Cerbone, Vincenzo; Macrì, Martina; Parrini, Matteo Maria (Lo Scalpello - Journal, 2021)
Periprosthetic fractures (PPF) constitute an issue of increasing importance for orthopedic surgeons. With the continuous advancement of less invasive surgery techniques and the progressively ageing population, prosthetic replacement procedures have become routine. PPF are complex conditions that can compromise the outcome of surgery and the patient’s quality of life. However, in some cases, revision surgery is required. In this article we will analyze the epidemiology, risk factors, different classi ications, management, and evolution of treatment of hip and knee periprosthetic fractures.